2017
DOI: 10.3892/mmr.2017.6939
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial growth medium suppresses apoptosis of mesenchymal stem cells in vitro via decrease of miR-29a

Abstract: The administration of mesenchymal stem cells (MSCs) in cases of cardiac ischemia/reperfusion injury (IRI) has been associated with a significant reduction of myocardial cell death and an effective improvement in cardiac function. However, one major limiting factor in MSCs transplantation therapy is the low survival rate of the transplanted cells. The present study aimed to demonstrate that human amnion-derived mesenchymal stem cells (hAMSCs) cultured with endothelial growth medium (EGM-2) exhibited reduced apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that the expression of miRNA‐29a decreased significantly in human amniotic mesenchymal stem cells (hAMSCs) exposed to serum‐free and hypoxi, and miRNA‐29a knockdown resulted in decreased apoptosis of hAMSCs by increasing myeloid cell leukemia‐1 (MCL‐1). The mechanism study shows that endothelial growth medium (EGM‐2) promoted the survival of hAMSCs partly through the regulation of miRNA‐29a and MCL‐1 expression levels . These studies show that miRNA‐29a plays a vital role in maintaining the normal functioning of HUVECs under normal and hypoxic environments.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies have shown that the expression of miRNA‐29a decreased significantly in human amniotic mesenchymal stem cells (hAMSCs) exposed to serum‐free and hypoxi, and miRNA‐29a knockdown resulted in decreased apoptosis of hAMSCs by increasing myeloid cell leukemia‐1 (MCL‐1). The mechanism study shows that endothelial growth medium (EGM‐2) promoted the survival of hAMSCs partly through the regulation of miRNA‐29a and MCL‐1 expression levels . These studies show that miRNA‐29a plays a vital role in maintaining the normal functioning of HUVECs under normal and hypoxic environments.…”
Section: Introductionmentioning
confidence: 88%
“…The mechanism study shows that endothelial growth medium (EGM-2) promoted the survival of hAMSCs partly through the regulation of miRNA-29a and MCL-1 expression levels. 13 These studies show that miRNA-29a plays a vital role in maintaining the normal functioning of HUVECs under normal and hypoxic environments. However, they focused on cell injury caused by hypoxia, which is distinct from endothelial injury caused by HG and also did not involve an HG model in vitro or in vivo.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation